Aktualisasi Pembelajaran Akidah Akhlak Sebagai Basis Pengembangan Karakter Anak Usia Dini Di Lembaga Paud Intan Pertiwi - Jimi Harianto; Masilawati; Santi Fadilah (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2025)
Early childhood is a critical period for establishing character through the internalization of Islamic faith and moral values. This study analyzes the implementation of Akidah Akhlak learning as a foundation for character development in children at the Intan Pertiwi Early Childhood Education Institution, with a focus on honesty, empathy, and discipline. Using a qualitative case study approach, data were collected through participant observation, in-depth interviews with teachers and parents, and curriculum documentation. The findings show that Islamic creed and ethics are taught through three main strategies: integrating values into daily routines, sharing stories of Islamic role models, and employing play- and singing-based contextual learning. These methods have effectively fostered positive behaviors, such as sharing, honesty, and respect, as well as increased discipline among children. The study concludes that teaching Islamic creed and ethics provides a strong basis for character development, with success relying on contextual approaches, teacher role modeling, and collaboration between schools and parents.